Advertising primed: how professional identity affects moral reasoning - Schauster, Erin (2022)
Moral reasoning among media professionals varies. Historically, advertising professionals score lower on the Defining Issues Test (DIT) than their media colleagues in journalism and public relations. However, the extent to which professional identity impacts media professionals’ moral reasoning has yet to be examined. To understand how professional identity influences moral reasoning, if at all, and guided by theories of moral psychology and social identity, 134 advertising practitioners working in the USA participated in an online experiment. While professional identity was not a significant predictor of moral reasoning, an interaction effect between gender and identity priming occurred. This finding suggests that we reconsider moral psychology theory’s explanatory power for media practitioners and consider how the complexity of professional identities in concert with gender and professional training, among other variables, interact to affect moral reasoning. In addition, advertising practitioners participating in this experiment scored higher on the DIT than those tested previously.